The notions of objectivity and journalistic voice in Arabic language hard news reporting - Alshehri, Abdulmohsin A. (LITERA, 2024)
A couple of widely-observed and much-discussed related notions within news journalism are "˜objectivity' and "˜journalistic voice'. They have been the focus of several linguistic and discourse analysis studies on English and across various languages and cultures. However, to date, they have not been thoroughly explored in Arabic news journalism. Therefore, this study attempts to close this gap by linguistically examining Arabic hard news reporting in relation to the key register features associated with these twin aspects. In particular, it is concerned with investigating patterns in the use of attitudinal language and attribution in such a journalistic tradition. To achieve this aim, it put together a corpus of thirty Arabic hard news reports collected from two prominent media organizations in the Middle Eastern region: Aljazeera and Alarabiya. It also drew on the insights offered by the Systemic Functional Linguistics (SFL)-based news journalism scholarship: specifically, the literature outlined in the Appraisal theory. The analysis carried out indicate that some Arabic hard news reports bear a similarity to English ones with respect to use of attitudinal meanings and modes of attribution. They operate in reporter voice, containing instances of inscribed authorial Appreciation and neutral and non-neutral reporting verbs.